2009
DOI: 10.1007/s12160-009-9103-x
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Generic Versus Tailored Interventions to Increase Colorectal Cancer Screening Among Intermediate Risk Siblings

Abstract: Individuals with a sibling who has had colorectal cancer diagnosed before age 61 are at increased risk for colorectal cancer and may derive particular benefit from screening. Tailored interventions may increase participation in appropriate colorectal cancer screening. This study evaluated the efficacy of two tailored interventions and a generic print intervention. Participant siblings (N = 412) who were not up-to-date with colorectal cancer screening were randomly assigned to receive either a generic print pam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
114
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(120 citation statements)
references
References 37 publications
4
114
1
1
Order By: Relevance
“…Consistent with other studies, our results indicate that prior CRCS experience predicts screening completion among those who were overdue at Year 1, as well as repeat, on-schedule screening at Year 2 (Vernon et al, 2011; Sifri et al, 2010; Manne et al, 2009; Myers et al, 2007). In the moderation analysis, prior CRCS had a stronger association with screening in the combined intervention groups compared with usual care, suggesting the intervention amplified the effect of prior screening experience.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with other studies, our results indicate that prior CRCS experience predicts screening completion among those who were overdue at Year 1, as well as repeat, on-schedule screening at Year 2 (Vernon et al, 2011; Sifri et al, 2010; Manne et al, 2009; Myers et al, 2007). In the moderation analysis, prior CRCS had a stronger association with screening in the combined intervention groups compared with usual care, suggesting the intervention amplified the effect of prior screening experience.…”
Section: Discussionsupporting
confidence: 91%
“…Of previous randomized controlled trials comparing a sociopsychologically tailored colorectal cancer screening intervention with an active control, 15,19,20,22,[25][26][27][28][29][30]33 only some reported improvements in screening, 19,25,28,29,34 in most instances based on patient report, 19,25,28,29 suggesting possible misclassification bias. These observations, plus our current findings, raise doubts about the superiority of sociopsychological tailoring to nontailored approaches in promoting colorectal cancer screening.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22] Whether enhancement of sociopsychological factors influences health behaviors is uncertain. 12,13,19,[22][23][24][25][26][27][28][29][30][31][32] Among trials comparing patients receiving sociopsychologically tailored colorectal cancer screening interventions with active control, 15,19,20,22,[25][26][27][28][29][30]33 only some found superior effects of tailoring 19,25,28,29,34 ; in all but 1 trial 34 screening was self-reported, 19,25,28,29 suggesting possible response bias. There is a need to examine further whether objectively measured colorectal cancer screening improves in response to sociopsychologi...…”
Section: Introductionmentioning
confidence: 99%
“…These items asked how strongly participants agreed or disagreed (on a five-point Likert-type scale) with statements about the cons of having a colonoscopy (e.g., “I would probably not have a colonoscopy if I had to have laxatives.”). There are six items in the previously published Fear of Colonoscopy Likert-type scale [31]. On a scale of one to five, participants were asked to rate how fearful they felt about issues related to colonoscopy (including the procedure, the preparation, etc.).…”
Section: Methodsmentioning
confidence: 99%